2012
DOI: 10.5688/ajpe768160
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Composition of the Editorial Boards of Leading Pharmacy Journals

Abstract: To the Editor. Serving on the editorial board of a peer-reviewed journal is a prestigious and influential position for those in academic pharmacy. Individuals are asked to occupy these positions based on their expertise, research, publications, and other accomplishments. Editorial board members have an important role because they provide peer review for submitted manuscripts and may suggest authors and topics for future publications. Studies have found that individuals from developing countries are underrepres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(54 citation statements)
references
References 3 publications
4
50
0
Order By: Relevance
“…[14,18,19] However, editorial bias is gaining more and more attention. [9,12,13,2023] Underrepresentation of individuals from low- and middle-income countries on editorial boards has been identified in leading subspecialty journals of several fields. [913] However, this situation has not yet been evaluated in leading spine journals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[14,18,19] However, editorial bias is gaining more and more attention. [9,12,13,2023] Underrepresentation of individuals from low- and middle-income countries on editorial boards has been identified in leading subspecialty journals of several fields. [913] However, this situation has not yet been evaluated in leading spine journals.…”
Section: Discussionmentioning
confidence: 99%
“…Leading journals in certain fields usually describe themselves as international journals, which was also found to be true in the field of spine surgery. [813] Therefore, five high-impact subspecialty spine journals in Journal Citation Reports (JCR) for the year 2016 were included in this study, [5,14] which followed the procedure of previous similar publications. [913] These leading spine journals included The Spine Journal (TSJ), Journal of Neurosurgery: Spine (JNS), European Spine Journal (ESJ), Spine , and Clinical Spine Surgery (CSS).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The average PubMed indexed publications in our study were 15.71. Dotson study 22 has found that the editorial board members (EBMs) of many leading international pharmacy journals have a very small number (<2%) of the members from lower-and middle-income countries. In our study, we observed that the faculty has been an EBM of 3.08 journals on an average.…”
Section: Discussionmentioning
confidence: 99%